Automatic Vehicle Location (AVL): Evaluation on the Punctuality Index of City Public Bus Service - Haziman, Zakaria; Diyana, Kamarudin,; Faiz, Azizul; Mohammad Fitri, Idrus; Nor Rokiah Hanum, Md Haron; Norhana Mohd, Aripin (Springer, 2023)
This study evaluates on-time bus service in ‘City A’, Malaysia using the punctuality index. Besides, the bus service reliability performance will also identify bus service punctuality characteristics for various operation conditions and routes in ‘City A’. City ‘A’ has been selected as this city lacks commuter and rail services, unlike Kuala Lumpur and the Klang Valley; thus, City A’s public bus service is in high demand. This article collected bus data using automatic vehicle location (AVL). Buses use SIM cards and mobile data networks to transmit location and time. GPS and fleet tracking system measure bus time and speed (FTS). Sampled bus system data was analysed to calculate punctuality indices for all routes. Different operating conditions affected bus punctuality. The punctuality index measures a stage bus’s service quality. Finally, the result of the study can be used to evaluate and improve public bus service.